2016
DOI: 10.1039/c6dt00312e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bishexadecyltrimethyl ammonium palladium tetrachloride based dual functional colloidal carrier as an antimicrobial and anticancer agent

Abstract: We have developed a dual function carrier using bishexadecyltrimethyl ammonium palladium tetrachloride, which has anticancer as well as antibacterial activity, using a ligand insertion method with a simple and easy work procedure. The complex is prepared by a simple and cost effective method using hexadecyltrimethyl ammonium chloride and palladium chloride under controlled stoichiometry. Herein, we report the aggregation (self assembly) of the metallosurfactant having palladium as a counter ion, in aqueous med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Kaur et al showed that the precipitation of Pd(II) and CTAC could be due to metalomicelles in water. 38 This is also observed for Pd-CTAB. 39,40 Importantly, Yagyu et al 40 suggested that the metal ion is found on the periphery moiety of micelles rather than core; i.e.…”
Section: Please Do Not Adjust Marginssupporting
confidence: 53%
See 1 more Smart Citation
“…Kaur et al showed that the precipitation of Pd(II) and CTAC could be due to metalomicelles in water. 38 This is also observed for Pd-CTAB. 39,40 Importantly, Yagyu et al 40 suggested that the metal ion is found on the periphery moiety of micelles rather than core; i.e.…”
Section: Please Do Not Adjust Marginssupporting
confidence: 53%
“…CTAC also reacts with PdCl 4 2− to form complex-surfactant postmicellar/organic salt aggregates. 38 Upon the addition of CTAC/NaOL to Na 2 PdCl 4 , the colour of the solution changed from yellow to orange and then it transformed into a orange precipitate. Kaur et al showed that the precipitation of Pd( ii ) and CTAC could be due to metalomicelles in water.…”
Section: Resultsmentioning
confidence: 99%
“…Another class of surfactants that has drawn much attention lately is metallosurfactants. This term is commonly used to designate compounds that behave as surfactants and contain a metal in their molecular structures as part of the headgroup (type 1), hydrophobic tail (type 2), or counterion (type 3) . Recent reports have revealed that metallosurfactants exhibit enhanced physicochemical properties compared to conventional surfactants. For this reason, metallosurfactants have been studied for a broad spectrum of applications such as catalysis, anticancer, and antimicrobial agents, , in nanoparticles synthesis, drug-delivery, , and templates for mesoporous materials. , When considering, in particular, dimeric surfactants, only two types of their metalloderivatives have been reported in the literature. Yi et al have investigated a homologous series of dimeric surfactants: m -2- m [XCl 3 Br] ( m = 14, 16, 18) with X = Fe, Ce, and Gd .…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer activity of micelle-forming complexes based on various metals and ligands has been investigated in a number of publications. ,− For these metallosurfactants, literature data are available on the significant role of structural factors (ligand composition, hydrophobicity, and nature of the metal) responsible for the anticancer activity of the complexes. Thus, for the human cervical cancer cell line (M-HeLa), the inhibitory concentration (IC 50 ) for the double-chain surfactant–ruthenium­(II) complexes is lower than that for the single-chain complexes…”
Section: Introductionmentioning
confidence: 99%